The Amphioxus Hox Cluster: Characterization, Comparative Genomics, and Evolution. - Amemiya, Chris T.; Prohaska, Sonja J.; Hill-Force, Alicia; Cook, April; Wasserscheid, Jessica; Ferrier, David E. K.; Pascual-Anaya, Juan; Garcia-Fernàndez, Jordi; Dewar, Ken; Stadler, Peter F.; Stadler, Peter F. (Wiley, 2008)
The amphioxus Hox cluster is often viewed as ‘‘archetypal’’ for the chordate lineage. Here, we present a descriptive account of the 448 kb region spanning the Hox cluster of the amphioxus Branchiostoma floridae from Hox14 to Hox1. We provide complete coding sequences of all 14 previously described amphioxus sequences and give a detailed analysis of the conserved noncoding regulatory sequence elements. We find that the posterior part of the Hox cluster is so highly derived that even the complete genomic sequence is insufficient to decide whether the posterior Hox genes arose by independent duplications or whether they are true orthologs of the corresponding gnathostome paralog groups. In contrast, the anterior region is much better conserved. The amphioxus Hox cluster strongly excludes repetitive elements with the exception of two repeat islands in the posterior region. Repeat exclusion is also observed in gnathostomes, but not protostome Hox clusters. We thus hypothesize that the much shorter vertebrate Hox clusters are the result of extensive resolution of the redundancy of regulatory DNA after the genome duplications rather than the consequence of a selection pressure to remove nonfunctional sequence from the Hox cluster.
This is the peer reviewed version of the following article: Amemiya, C.T., Prohaska, S.J., Hill-Force, A., Cook, A., Wasserscheid, J., Ferrier, D.E.K., Pascual-Anaya, J., Garcia-Fernàndez, J., Dewar, K. and Stadler, P.F. (2008), The amphioxus Hox cluster: characterization, comparative genomics, and evolution. J. Exp. Zool., 310B: 465-477., which has been published in final form at https://doi.org/10.1002/jez.b.21213. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. This article may not be enhanced, enriched or otherwise transformed into a derivative work, without express permission from Wiley or by statutory rights under applicable legislation. Copyright notices must not be removed, obscured or modified. The article must be linked to Wiley’s version of record on Wiley Online Library and any embedding, framing or otherwise making available the article or pages thereof by third parties from platforms, services and websites other than Wiley Online Library must be prohibited.
Keywords: Genoma; Biología marina; Cordados; Hox evolution; Hox; Hox cluster; Amphioxus; Comparative genomics; Evolution; Chordates